Strategic Influence on Enterprise Business of Carriers Under New Technologies Trend - Luo, JianQiu (2016)
New technologies such as mobility in working style, big data, internet connection and cloud service etc are shaping and inspiring new ways to create and run business today. Technological innovation is always driven by business demand. It leads to generate new ICT services from carriers in B2B area. Under such huge booming development of technological innovation, top carriers are facing revenue decline and traditional business is shrinking. This new trend has imposed great pressure in business management to top carriers. They are looking for new growth in profit making engines and trying to transform existing telecom business to adapt the global digitalization market trends. Cloud computing service to enterprise management is obviously a potential way emerged from global business operation. However, in order to complete the business transformation, carriers have to face direct competition from existing cloud service providers in the market. Giant OTT companies like Amazon has built up deep and wide connection network with enterprise customers via high quality Amazon Web Service. How to break into the existing B2B market in order to get more market share and increase revenue? This would require carriers to establish a strong and complete ICT ecosystem, surrounding by infrastructure vendors, sales channels, industry software developers, service partners, etc. Strategic analysis has been conducted using various business models in the study, by comparison with various examples of top global carriers such as DT, BT, Vodafone, FT and Telefonica. By taking gap analysis, market insight, strategic intent, business design and key task, this study has provided some insights into the business. At the end of the study, it has indicated several strategic implications. This study would be helpful for either employee or high level management carriers in B2B area, it has brought up new concept and new angle of thinking.